A review of recent and emerging antimicrobial nanomaterials in wastewater treatment applications. (September 2021) - Yusuf, Ahmed; Al Jitan, Samar; Garlisi, Corrado; Palmisano, Giovanni
Abstract: In this paper, we present a critical review on antimicrobial nanomaterials with demonstrated potential for application as a disinfection technology in wastewater treatment. Studies involving fabrication and testing of antimicrobial nanomaterials for wastewater treatment were gathered, critically reviewed, and analyzed. Our review shows that there are only a few eligible candidate nanoparticles (NPs) (metal and metal oxide) that can adequately serve as an antimicrobial agent. Nanosilver (nAg) was the most studied and moderately understood metal NPs with proven antimicrobial activity followed by ZnO (among antimicrobial metal oxide NPs) which outperformed titania (in the absence of light) in efficacy due to its better solubility in aqueous condition. The direction of future work was found to be in the development of antimicrobial nanocomposites, since they provide more stability for antimicrobial metal and metal oxides NPs in water, thereby increasing their activity. This review will serve as an updated survey, yet touching also the fundamentals of the antimicrobial activity, with vital information for researchers planning to embark on the development of superior antimicrobial nanomaterials for wastewater treatment applications. Highlights: Antimicrobial activity of metal and metal oxide NPs depend on metal ions and ROS. Emerging antimicrobial nanocomposites show better wastewater disinfection. Future work should focus on the synthesis of advanced antimicrobial nanocomposite.